Eosinophil/Monocyte Ratio Combined With Serum Thyroid Hormone for Distinguishing Graves' Disease and Subacute Thyroiditis - Hu, Yongbin; Zhou, Diyi; Chen, Jiawei; Shan, Pengfei (Frontiers in Endocrinology, 2020)
Objective: Thyrotoxicosis is commonly classified into several entities according to different etiologies. Identifying the causes of thyroid dysfunction is critical for the subsequent selection of treatment. The free triiodothyronine to free thyroxine ratio (fT3/fT4) is widely used but is still a controversial diagnostic measurement. Methods : A total of 290 patients, 141 healthy control subjects, 86 patients with untreated Graves’ disease (GD,) and 63 patients with subacute thyroiditis (SAT) were enrolled in the study. The main aim was to evaluate the diagnostic value of different indexes from serum testing including fT3, fT4, eosinophils (Eo) and monocytes (Mo). The diagnostic performance of multiple indexes was evaluated separately using receiver operating characteristic curve analysis. Results: Among all the indexes studied, a combination indicator of optimum cut-off value at 0.561 gave the best diagnostic value, reaching sensitivity and specificity of 89.53% and 90.48%, respectively, followed by an optimum cut-off fT4/fT3 ratio at 2.841, which yielded a sensitivity of 80.23% and a specificity of 88.89%. An equation of combination indicators was developed to calculate the probability value. Conclusion: Compared to regular indexes (fT4/fT3 and Mo/Eo), the combination indicator provided a higher prediction probability, which may serve as a simple, cost-effective tool for differentiating GD from SAT patients, especially in undeveloped regions of China.